Federalizing the muse : United States arts policy and the National Endowment for the Arts, 1965-1980 - Binkiewicz, Donna M. (University of North Carolina Press, 2004)
The National Endowment for the Arts is often accused of embodying a liberal agenda within the American government. This text assesses the leadership and goals of Presidents Kennedy through Carter, as well as Congress and the National Council on Arts, covering the players who created national arts policy.